Social-ecological resilience for well-being : a critical realist case study of Boksburg Lake, South Africa - Fox, Helen Elizabeth (Rhodes University, Faculty of Science, Institute for Water Research, 2015)
This thesis is based on a case study of the degraded Boksburg Lake social-ecological system and an environmental education initiative that aimed to support its transformation. This initiative aimed to involve local people in reclaiming the lake's social and ecological value, through a process of collectively reimagining possibilities, shaping identities, gaining knowledge and developing local human agency. The focus was on social learning processes in schools and churches to explore opportunities for co-engaged reflexivity that might produce transformation. Schools and Christian churches, two institutions that reflect modern, western socialecological worldviews also have the potential to bring about change. Critical Realism was chosen as my philosophical framework as it provided the tools to explore deeper mechanisms beyond empirical reality, both influencing the degrading trajectory as well as providing possibilities for transformation. It also legitimised case study research as a means to understand more generalised processes characterising modern social-ecological systems. The choice of Critical Realism informed the scope of my primary research question: What generative mechanisms constrain and enable the development of social-ecological resilience for well-being, in the modern social-ecological system of Boksburg Lake? The following three goals were formulated to address this primary question. Goal 1: Based on a multitheoretical perspective of social-ecological literature, develop conceptual tools that have explanatory power to probe generative mechanisms operating in the Boksburg Lake social-ecological system. Goal 2: Identify generative mechanisms driving the current degradation of the Boksburg Lake social-ecological system. Goal 3: Identify learning mechanisms that support transformation for greater social-ecological resilience of the Boksburg Lake social-ecological system. By addressing the primary question and research goals I aimed to gain insights into modern global socialecological systems, the mechanisms that drive high social-ecological risk and the requirements for and possibilities of global systemic change. Drawing on a broad reading of social-ecological literature from different vantage points, tools with explanatory power were developed to probe for generative mechanisms in the Boksburg Lake social-ecological system (goal 1). The human capacity for symbolic representation is identified as an emergent property of coevolving human-ecological systems. These symbolic representations become expressed in culture and worldviews, and influence patterns of identifying, types of knowledge and forms of agency. The nature of these will determine the degree that cultural systems are embedded within ecological reality and the extent of cultural-ecological coupling. A cultural system closely coupled with ecological realities is likely to value ecological systems and manage them for their health, while less coupled cultural-ecological systems are likely to lead to the opposite. Because of their integrated nature, the extent of ecological health and value will affect the decline or sustainability of cultural-ecological systems. There are numerous examples of the learning that can take place when cultural-ecological systems are facing decline. This learning can enhance or reduce biophyllic instincts that become encoded in patterns of identifying, types of knowledge and forms of agency. This in turn affects the strength of cultural-ecological coupling and the extent that human societies co-evolve with ecological systems.,Normalising ideologies is a concept coined in the thesis to refer to symbolic representations of reality that have become integral to a social fabric and determine meaning, while maintaining the domination of the powerful. These ideologies determine patterns of identifying, knowledge and agency and are recognised as having a fundamental influence on the resilience of social-ecological systems. Four normalising ideologies are identified that promote apparent human progress at the expense of ecological integrity and social equality and thus alienation with each other and the ecological world. These are human-ecological dualism, anthropocentrism, nature is mechanised and nature is to be controlled. There are also a number of ideologies promoting connectedness with the ecological world that, if they became normalised, would support greater social-ecological resilience for well-being. Generative mechanisms driving the current degradation of the Boksburg Lake socialecological system were identified (goal 2). Drawing on critical methodology, the main method adopted was document analysis of the Boksburg Advertiser archives, Boksburg's local newspaper. Four generative mechanisms are recognised as most influential. Two of these have been named hegemonic symbolic systems. The primary symbolic system consists of the four normalising ideologies, mentioned above, that promote human progress at the expense of ecological health. The secondary, more explicit symbolic system, built on this, consists of the following normative ideologies: economic growth is imperative, unrestrained development is promoted, competition is the necessary means and consumerism is the good life. These two symbolic systems have had causal influence on the systematic erosion of ecological processes and biological diversity that has occurred in Boksburg, with the consequent undermining of social-ecological resilience for well-being. The third mechanism that constrains resilience is the power dynamics that have shaped Boksburg's economic history and social-ecological system. This has resulted in a society built on inequality and injustice with all its associated social and environmental ills, expressed as externalities. The fourth mechanism resides in Boksburg's political and municipal dynamics. These structures are not designed to tackle complex social-ecological problems and they hold considerable agential power, yet seem dysfunctional at present. Learning mechanisms that support transformation for greater social-ecological resilience of the Boksburg Lake social-ecological system were identified (goal 3). By adopting the role of a reflexive practitioner, supported by action research, case study and interpretivist methodologies, data on the empirical manifestations of the environmental educational initiative were collected. Methods included semistructured interviews, focus groups, document analysis and participant observation. Findings indicate that schools and churches are important institutions that can positively influence patterns of identifying, knowledge about and agency for Boksburg Lake and can thus play a role in transforming hegemonic normalising ideologies. Important learning mechanisms identified included: Learning reflexively together within communities of practice that provide opportunities for active rather than passive learning; involving the youth as they are a group of people with notable enthusiasm, vision, energy and motivation; learning through information acquisition, investigation, action and deliberation; learning about abstract concepts and theoretical knowledge but embedding this in local realities; and learning that provides reference markers for how things can be different.
Keywords: Boksburg Lake and Wetland project; Reservoirs -- South Africa -- Boksburg; Water -- Pollution -- South Africa -- Boksburg; Human ecology -- South Africa -- Boksburg; Social learning -- South Africa -- Boksburg; Critical realism